Pollen-foraging preferences of honey bee colonies (Apis mellifera L.) based on plant bloom timing in an urbanized Northeast U.S. habitat - Cole F.P. Moran-Bariso; David C. Gilley (PLoS ONE, 2025)
To successfully provision the colony with protein and other essential nutrients, honey bee colonies track ephemeral floral food sources and make adaptive group decisions about which pollen species to reject, which to collect, and in what quantities. This descriptive study has two objectives; 1) to document pollen diet-choice decisions (both acceptance and rejection) in freely foraging honey bee colonies at high temporal resolution over an entire foraging season, and 2) to create a phenological calendar for the mutualism between honey bees and their pollen-food source plants that can be used to assess possible future phenological mismatch. We used pollen traps to harvest pollen weekly from two honey bee colonies from May until October (2023) to determine the relative abundances of pollen sources utilized. We simultaneously monitored in the field plant-bloom timeframes of 41 known honey bee pollen-source plants within the colonies’ foraging range. Honey bees collected at least 33 plant species in detectable amounts, with an average of 6 species in any single 24-hour colony harvest. An average of 13.7 known food sources were in bloom per week, with foragers utilizing 5.6 sources on average per week, showing that rejection of food sources is a major element of pollen-diet choice. The identity of accepted and rejected sources fluctuated every week. Foragers adopted novel pollen source species constantly throughout the season, on average 2.3 new sources per week, suggesting effective tracking of ephemeral floral sources which was intertwined with reliance on a set of abundant perennial herbs. These data provide a unique high-resolution picture of adaptive group foraging decisions in honey bees over an entire foraging season. Pollinator diet-choice dynamics are increasingly important to understand because they not only drive angiosperm reproduction in both natural and agricultural ecosystems but also are expected to be impacted strongly by climate change.